Race and access to mental health and substance abuse treatment in the criminal justice system. Issue 2 (17th February 2016) - Thompson, Melissa; Newell, Summer; Carlson, Matthew J.
ABSTRACT: We study racial disparities in treatment for substance abuse/mental illness in the justice system by interviewing Parole Officers (POs). POs report financial and cultural barriers to mental health treatment for most parolees, but suggest that substance abuse treatment is adequate. Inadequacies regarding culturally competent providers are noted, and these inadequacies may affect retention and success in treatment. POs' race can affect interpretations of race-based disparity and many POs struggle with believing parolees who report racist treatment. Results suggest more research to understand the unique experiences parolees of color face as they navigate the mental health and substance abuse treatment environment.